2019
DOI: 10.1093/jnci/djz166
|View full text |Cite|
|
Sign up to set email alerts
|

Prediagnostic Plasma Bile Acid Levels and Colon Cancer Risk: A Prospective Study

Abstract: Background Bile acids have been proposed to promote colon carcinogenesis. However, there are limited prospective data on circulating bile acid levels and colon cancer risk in humans. Methods Associations between prediagnostic plasma levels of 17 primary, secondary, and tertiary bile acid metabolites (conjugated and unconjugated) and colon cancer risk were evaluated in a nested case-control study within the European Prospectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
66
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 89 publications
(69 citation statements)
references
References 23 publications
3
66
0
Order By: Relevance
“…A separate investigation, published in the same journal, identified an association between prediagnostic bile acid concentrations and colon cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. 10 These observations are supported by experimental models demonstrating that bile acids are critical to the gut-liver-axis, and may contribute to the pathogenesis of liver, colorectal and perhaps other digestive diseases. 11 These exciting results provide plausible mechanisms linking coffee drinking to gastrointestinal cancer, and merit replication in future studies.…”
Section: Mainmentioning
confidence: 80%
“…A separate investigation, published in the same journal, identified an association between prediagnostic bile acid concentrations and colon cancer risk in the European Prospective Investigation into Cancer and Nutrition (EPIC) cohort. 10 These observations are supported by experimental models demonstrating that bile acids are critical to the gut-liver-axis, and may contribute to the pathogenesis of liver, colorectal and perhaps other digestive diseases. 11 These exciting results provide plausible mechanisms linking coffee drinking to gastrointestinal cancer, and merit replication in future studies.…”
Section: Mainmentioning
confidence: 80%
“…The five-year survival rate at early diagnosis is 90%, and the incidence of distant metastasis is less than 10% [ 19 ]. Specific tumor biomarkers are urgently needed to help enable early diagnosis of colorectal cancer, selection of "personalized" treatment strategies, and to predict prognosis [ 20 22 ]. In the present study, we analyzed the sequencing data of colon cancer in the TCGA database and found that GSPT1 was abnormally highly expressed in colon cancer tissue and related to tumor size.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our results are in line with the published in vivo data and add to the body of evidence that antagonizing M3R not only prevents de novo tumor formation but may indeed be a tool to treat CRC in a clinical setting. Finally, since bile acids present intraluminally promote CRC tumorigenesis, antagonizing bile acid-induced M3R activation may add to the benefit of darifenacin [38,39].…”
Section: Discussionmentioning
confidence: 99%